1991
DOI: 10.1159/000243318
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Plasma Apolipoproteins B and A-I in Fetal Bovines

Abstract: Plasma lipid, apolipoprotein (apo) B and apo A-I concentrations were measured in fetal calves in the age range of 4–9 months. The results were compared with those obtained from preruminant calves and cows. The studied lipids and apolipoproteins underwent quantitative changes during development. Fetal calves, as compared to preruminant calves and cows, had a particularly low apo A-I concentration and a high apo B/apo A-I ratio. Unlike adult animals which have two forms of apo B, fetal calves had only high molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Contrary to rat where the intensity of the hepatic editing process changed during development and with age [10], liver of fetal or adult bovines seemed unable to realize these processes [12,30]. These results were in complete agreement with results showing the only presence of the high molecular form of apo B (apo B100) in the plasma of fetal calves [14].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Contrary to rat where the intensity of the hepatic editing process changed during development and with age [10], liver of fetal or adult bovines seemed unable to realize these processes [12,30]. These results were in complete agreement with results showing the only presence of the high molecular form of apo B (apo B100) in the plasma of fetal calves [14].…”
Section: Discussionsupporting
confidence: 72%
“…In cultured human [28] and rat [33] hepatocytes or in HepG2 cells [34], these hormones were shown to alter apo B synthesis and secretion by inhibiting apo B mRNA translation [28,34] and by enhancing neosynthesized apo B degradation [33,34]. Such effects would explain, partly, the net decrease in plasma levels of apo B [14] and in LDL rich in apo B [35] found in fetal calves during the last weeks of fetal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study a significant (p≤0.01) increase was observed in the expression of apo A-I in the plasma of calves during the first week of life. Marcos et al (1991) reported, that concentration of apo A-I in the bovine fetal plasma was maintained on a steady level during the whole gestation period and it was considerably lower when compared with plasma apo A-I concentration in calves during the early postnatal period. The authors postulated that the observed phenomenon was primarily related to the increase in the HDL particle size.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that humans affected by liver diseases frequently show an abnormal apolipoprotein profile (1,16). We recently proposed a quantitative assay for these apolipoproteins in bovines (17,18). Hence, the objective of this study was to examine the relationship between fatty liver and apo B and apo A-I serum concentrations.…”
mentioning
confidence: 99%